2013
DOI: 10.1177/1934578x1300800428
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Emotional Behavior and Stress by Inhalation of the Essential oil from Chamaecyparis obtusa

Abstract: Various effects have been reported in the literature for the essential oil from Chamaecyparis obtusa (EOCO), such as antibacterial and antifungal activity. In this study, we examined the effect of EOCO on emotional behavior and stress-induced biomarkers. Male ICR mice, aged 5 weeks at the start of each experiment, were individually housed in cages for 1 week. After placing each mouse in a glass container and exposing it to EOCO for 90 min, we then investigated the influence on emotional behavior using the elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…The GC‐MS/FID analysis of our F. angulata essential oil indicated monoterpene hydrocarbons, including α‐pinene (24.10%), β‐pinene (22.70%), α‐phellandrene (12.10%) and β‐phellandrene (20.50%), which accounted for 79.40% of the total essential oil, as the main components of the essential oil suggesting that these constituents could be responsible for the observed anxiolytic‐antidepressant‐like behaviour in scopolamine‐treated rats. Among these monoterpenes, α‐pinene (24.10%) was identified in high amounts and it has been reported to present anxiolytic effects . The monoterpene β‐pinene (22.70%) identified in our essential oil as the main active compound showed antidepressant‐like and sedative‐like activity as previously reported …”
Section: Discussionsupporting
confidence: 82%
“…The GC‐MS/FID analysis of our F. angulata essential oil indicated monoterpene hydrocarbons, including α‐pinene (24.10%), β‐pinene (22.70%), α‐phellandrene (12.10%) and β‐phellandrene (20.50%), which accounted for 79.40% of the total essential oil, as the main components of the essential oil suggesting that these constituents could be responsible for the observed anxiolytic‐antidepressant‐like behaviour in scopolamine‐treated rats. Among these monoterpenes, α‐pinene (24.10%) was identified in high amounts and it has been reported to present anxiolytic effects . The monoterpene β‐pinene (22.70%) identified in our essential oil as the main active compound showed antidepressant‐like and sedative‐like activity as previously reported …”
Section: Discussionsupporting
confidence: 82%
“…We previously reported that the essential oil from Chamaecyparis obtusa reduced stress and had an anxiolytic‐like action. Moreover, that study demonstrated α‐pinene, one of the main components of the essential oil from Chamaecyparis obtusa , to have an anxiolytic‐like action (Kasuya et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…[1][2][3][4][5][6] We recently found that in vivo transferability by inhalation administration varies depending on the type of volatile compounds. It has been reported that essential oils of coniferous trees, juniper, lavender and sandalwood have anxiolytic-like activities, and the chemical components exhibiting these effects are reported to be linalool, linalyl acetate, a-pinene and a-santalo.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that essential oils of coniferous trees, juniper, lavender and sandalwood have anxiolytic-like activities, and the chemical components exhibiting these effects are reported to be linalool, linalyl acetate, a-pinene and a-santalo. [1][2][3][4][5][6] We recently found that in vivo transferability by inhalation administration varies depending on the type of volatile compounds. 7 For example, 1,8-cineole is not readily metabolized from within the brain, even at 30 min after inhalation.…”
Section: Introductionmentioning
confidence: 99%